Two new species of Steinernema Travassos, 1927 from the humid forest of southern Cameroon - Ngo Kanga, F.; Trinh, P.Q.; Waeyenberge, L.; Spiridonov, S.E.; Hauser, S.; Moens, M. (2012)
Steinernema cameroonense sp. n. and S. nyetense sp. n. are two new species isolated from soil samples in Minkama, Obala and Nkontangan, Nyété, respectively. Steinernema cameroonense sp. n. is characterised by infective juvenile body length averaging 622 (490-693) μm; pharynx length of 108 (100- 114) μm; tail length of 76 (52-107) μm; D and E values of 48 (42-56) and 75 (48-116), respectively. The lateral field pattern is 2, 4, 5, 6, 3, and 2. First generation males can be recognised by spicule length of 69 (51-85) μm; GS = 64 (47-76); SW = 170 (131-200); D 64 (48-76). Steinernema nyetense sp. n. is characterised by infective juvenile body length averages 648 (565-708) μm; pharynx length is 114 (104- 127) μm; tail length is 82 (54-112) μm; D and E values are 46 (37-50) and 66 (43-89), respectively. The lateral field pattern is 2, 4, 5, 4, 3, and 2. First generation males can be recognised by spicule length of 80 (67-98) μm; GS = 66 (51-77); SW = 198 (124-283); D = 55 (40-70). As inferred from the sequence analysis of ITS rDNA S. cameroonense n. sp. and S. nyetense sp. n. represent separate group in the genus Steinernema distantly related to ‘monticolum’ and ‘feltiae-kraussei-oregonense’ clades. According to D2D3 LSU rDNA sequences the two new Steinernema species from Cameroon constitute a separate group related to inner nodes of Steinernema phylogeny.